2011
DOI: 10.1371/journal.pone.0014568
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Expression during Early Cerebral Ischemia-Reperfusion in Rats: Enhanced Expression in the Right Cortex Is Suppressed by Acetaminophen

Abstract: Osteopontin (OPN) is a pleiotropic protein implicated in various inflammatory responses including ischemia-reperfusion (I-R) injury. Two distinct forms of the protein have been identified: an extensively studied secreted form (sOPN) and a less-well-known intracellular form (iOPN). Studies have shown that increased OPN expression parallels the time course of macrophage infiltration into injured tissue, a late event in the development of cerebral infarcts. sOPN has been suggested to promote remodeling of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Notably, Baliga et al . proposed that the intracellular form of OPN is increased in the cytoplasm of the cortex during early cerebral ischaemia-reperfusion, suggesting a role of OPN as a responder to stroke-induced cell damage83. Thus, we speculate that degenerating neurons could be the initial source of the OPN protein localised within dendritic mitochondria, but it remains to be established whether this indeed reflects the presence of intracellular OPN.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, Baliga et al . proposed that the intracellular form of OPN is increased in the cytoplasm of the cortex during early cerebral ischaemia-reperfusion, suggesting a role of OPN as a responder to stroke-induced cell damage83. Thus, we speculate that degenerating neurons could be the initial source of the OPN protein localised within dendritic mitochondria, but it remains to be established whether this indeed reflects the presence of intracellular OPN.…”
Section: Discussionmentioning
confidence: 75%
“…[86][87][88] Previous studies have demonstrated that OPN is involved in iNOS pathway. 50,89,90 Induced OPN provides a dose-dependent pattern suppressing iNOS expression after acute brain injury 65,80 by increasing expression of integrin-β1 and then inhibiting the Janus kinase/signal transducers and activators of transcription…”
Section: Opn and Neuroinflammationmentioning
confidence: 99%
“…The upregulation of OPN has been reported in rat retina that activated microglia on I–R, 11 in cardiomyocytes in an ex-vivo hemoperfused working porcine heart model, 12 in the brain during early cerebral I–R in rats 13 but also in cultured rat aortic vascular smooth muscle cells in response to hypoxia. 14 The role of OPN in I–R injury has largely been reported in the kidney and could have an unexpected protective and deleterious role.…”
mentioning
confidence: 92%